New insights into the understanding of MHC associations with immune‐mediated disorders. (January 2017) - Caillat‐Zucman, S.
Abstract: Recent advances in technologies such as high density array‐based genotyping, DNA and RNA deep sequencing, expression quantitative‐trait loci mapping, epigenome analyses, and new computational strategies, have introduced drastic shifts into our understanding of major histocompatibility complex (MHC) association with immune‐mediated diseases. Here, we review the most exciting findings in this field. We show how the fine characterization of structural features and expression levels of MHC alleles, posttranslational or environmental modifications of HLA‐bound peptides, and epistatic interactions with non‐HLA genes, has made it possible not only to provide mechanistic explanations for MHC associations with immune‐mediated diseases but also to help choose relevant therapeutic targets.